Altered peripheral B lymphocyte homeostasis and functions mediated by IL‐27 via activating the mammalian target of rapamycin signaling pathway in patients with rheumatoid arthritis. (5th October 2021) - Tang, Yawei; Bai, Ziran; Qi, Jingjing; Lu, Zhimin; Ahmad; Wang, Guan; Jin, Minli; Wang, Bing; Chen, Haifeng; Li, Xia
Abstract: B cell dysfunction and inflammatory cytokine over‐production participate in the pathogenesis of rheumatoid arthritis (RA). Here we compared peripheral B cell homeostasis and immune functions between RA patients and healthy controls (HC) and explored vital signaling pathways involved in altered RA B cells. We found that RA patients showed significantly decreased frequencies of peripheral CD19 + CD27 + CD24 high regulatory B (Breg) cells but increased frequencies of CD19 + CD27 + CD38 high plasmablasts and CD19 + CD138 + plasma cells, and higher levels of serum immunoglobulin (Ig)M and IgG. Compared to HC peripheral B cells, RA peripheral B cells had more increased proliferation and higher expression of activation markers. Importantly, our results showed that RA peripheral B cells displayed the mTOR signaling pathway to be more activated, and inhibition of mTOR could restore RA B cell homeostasis and functions. RA serum‐treated B cells exhibited more increased expressions of mTOR, which could be restored with the addition of anti‐interleukin (IL)‐27 neutralizing antibody. Serum IL‐27 levels were significantly increased in RA patients and positively correlated with disease activity, the frequencies of plasma cells and the levels of autoantibodies. In vitro, IL‐27 notably promoted immune dysfunction of RA B cells, which were inhibited by anti‐IL‐27 neutralizing antibody. Also, the mTOR pathway was more activated in IL‐27‐treated RA B cells, and mTOR inhibition apparently reversed abnormalities of RA B cells mediated by IL‐27. These results suggest that increased serum IL‐27 levels could promote peripheral B cell dysfunction in RA patients via activating the mTOR signaling pathway. Thus, IL‐27 may play a pro‐pathogenic role in the development of RA, and antagonizing IL‐27 could be a novel therapy strategy for RA. Abstract : RA B cells showed altered peripheral B cell homeostasis and functions via activating mTOR signaling pathway. Increased levels of IL‐27 in RA serum promoted immune dysfunctions of B cells through the activation of mTOR signaling pathway. IL‐27 may play a vital role in the pathogenesis of RA, and will be a candidate cytokine for targeted therapy in future.